[OP.5B.01] PULSE WAVE VELOCITY AND DEPRESSION IN HYPERTENSIVE PATIENTS. (September 2017) - Greco, A.; Maloberti, A.; Varrenti, M.; Lucente, D.; Pessina, L.; Peretti, A.; Franzosi, C.; Mondellini, G.; Palazzini, M.; Laurent, S.; Boutouyrie, P.; Steca, P.; et al.
Abstract : Objective: Abnormal large artery function plays an important role in the pathogenesis of cardiovascular (CV) diseases. Prior studies have suggested that the principal determinants of arterial stiffening are age, Blood Pressure (BP) and others CV risk factors such as dyslipidemia and diabetes. However, scanty data are available on the role of psychological factors on arterial stiffness. Previous work have shown that arterial stiffness was associated with depression in the elderly and in healthy adolescents, but no study has focused on the role of depression and other psychological variables in hypertensive patients. The aim of the current cross-sectional study was to evaluate the association between depression, anxiety, perceived stress, Type A personality, and Type D personality and Pulse Wave Velocity (PWV) in a cohort of hypertensive patients, using baseline examination data of the TIPICO project. Design and method: A total of 259 outpatients (ages 18–80 years) followed by the Hypertension Unit of S. Gerardo Hospital (Monza, Italy) affected by essential hypertension were recruited. Aortic stiffness was evaluated by PWV between the carotid and the femoral artery of the same side with the patient in the supine position. Moreover, anamnestic data, clinical BP, and laboratory data were evaluated. Patients were asked to complete a battery of psychological questionnaires under the guidance of a psychologist. The associations between psychological variables and PWV was explored using multivariate stepwise linear regression analysis and regression coefficients (b) were given per 1-point increment. Results: The mean age was 55.9 ± 10.1years, SBP and DBP were 135.6 ± 17.7 and 82.5 ± 9.1mmHg and PWV was 8.6 ± 2.1m/s. The results from the multivariate stepwise linear regression analysis showed that age (beta = 0.284, p < 0.001), pulse pressure (beta = 0.369, p < 0.001), dyslipidemia (beta = 0.130, p = 0.012), family history of CV disease (beta = -0.123, p = 0.017), and depression (beta = 0.126, P = 0.014) were significantly and independently associated with PWV. Conclusions: The current study shows that, among psychological factors, higher levels of depression is related to higher PWV, while anxiety, perceived stress, Type A personality, and Type D personality are not associated with arterial stiffness. Depression assessment and target intervention to reduce it are recommended in hypertensive patients.